Exploring A High School Teacher’s Experience in Teaching Speaking Through Project-Based Learning: A Narrative Inquiry - Wulandari, Rindi Fatikha; Ahmad, Yousef Bani; Mobit, Mobit (FKIP - Universitas Riau, 2025)
This narrative inquiry delves into the lived experience of an English teacher navigating the implementation of Project-Based Learning (PjBL) to enhance speaking competence within a unique, nature- and science-integrated high school in Indonesia. Addressing the pedagogical gap prevalent in traditional EFL settings—characterized by limited authentic exposure and teacher-cantered methods—the study sought to illuminate the teacher’s practices, the specific challenges encountered in a non-conventional context, and the adaptive strategies employed. Utilizing a qualitative methodology, data were meticulously collected through semi-structured interviews, intensive classroom observations, and document analysis (including lesson plans and project artifacts). The findings unequivocally demonstrate that PjBL is instrumental in promoting authentic language use and heightened student engagement through real-life tasks, such as presentation and video projects. Crucially, the teacher adopted dynamic, constructivist roles—shifting fluidly between facilitator, guide, and evaluator. The primary implementation hurdles identified were stringent time management demands, accommodating diverse speaking proficiency levels, and managing fluctuating student motivation. These were mitigated successfully via adaptive lesson planning, targeted group scaffolding, the strategic integration of digital tools, and the consistent provision of immediate feedback. This research provides a teacher-centered perspective that significantly contributes to the literature by validating PjBL’s efficacy and adaptability within complex, interdisciplinary EFL environments.